Studying the Effect of Organizational Justice on Manpower Maintenance in Birjand University of Medical Sciences - Abdolali Keshtegar (Journal of Global Pharma Technology, 2018)
Manpower is considered as one of the basic and important resources of organizations. In order to reach their goals, organizations need specialized and committed human force to achieve their goals. Therefore, one of the most important duties of organizations regarding the management of human resources is manpower maintenance. To this end, the present study has aimed to investigate the effect of organizational justice and its dimensions on manpower maintenance in Birjand University of Medical Sciences. The present study is an applied research in terms of its objective and it is a descriptive survey in terms of its data collection method. The statistical population of this research has been composed of the employees of Birjand University of Medical Sciences. 150 of these employees were selected as the research sample using the judgmental sampling method. In order to test the hypotheses, the Pearson correlation coefficient and the multivariate regression analysis were used. The results obtained from the Pearson correlation coefficient showed that there is a positive and significant relationship between organizational justice and manpower maintenance (r=79.3). Also, the results of multivariate regression analysis have shown that interactive justice, procedural justice and distributive justice variables have been able to separately explain 50.3, 30.5 and 20.6 percent of the scores of the maintenance system, respectively. In other words, among the components of organizational justice, interactive justice has had the most substantial impact on manpower maintenance and distributive justice had the least substantial effect on it in the population under study.Keywords: Organizational justice, Procedural justice, Distributive justice, Interactive justice, Man power management.